2020
DOI: 10.1038/s41598-020-74889-x
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study on diabetes epidemiology among people aged 40 years and above in Shenyang, China

Abstract: This study aimed at understanding the diabetic prevalence, awareness, treatment and control rates and their influencing factors among people aged ≥ 40 years in Shenyang, China. A face-to-face cross-sectional epidemiological survey was conducted on the respondents using the national unified questionnaire. A total of 3922 respondents were enrolled, including 609 cases of diabetes. The diabetic prevalence rate was 15.5%, and was higher in rural areas than that in urban areas (17.7% vs. 14.2%, p = 0.004), while no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Research across different regions, age groups, and socioeconomic statuses in China has found that awareness of DM in the rural elderly is insufficient, which leads to a lack of treatment and control of the disease. The high prevalence and low awareness, control, and treatment rate of DM have increased the risk thereof in this population [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…Research across different regions, age groups, and socioeconomic statuses in China has found that awareness of DM in the rural elderly is insufficient, which leads to a lack of treatment and control of the disease. The high prevalence and low awareness, control, and treatment rate of DM have increased the risk thereof in this population [23][24][25][26][27].…”
Section: Discussionmentioning
confidence: 99%
“…35 In some epidemiological studies in Asian countries, the rate of treatment adherence for diabetes was lower in males than in females, even though the prevalence of diabetes was higher in males than in females. 36,37 Thus, it could be presumed that depressive symptoms have more of an impact on diabetes management in males. When HbA1c gradually improved from W1 to W2, depressive symptoms were observed to decrease in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Health‐related needs and individual experiences differ by sex, and males often seem to perceive existing services and programs for older adults as being female‐specific 35 . In some epidemiological studies in Asian countries, the rate of treatment adherence for diabetes was lower in males than in females, even though the prevalence of diabetes was higher in males than in females 36,37 . Thus, it could be presumed that depressive symptoms have more of an impact on diabetes management in males.…”
Section: Discussionmentioning
confidence: 99%
“…At the same time, the population with prediabetes represents a large reservoir of patients at risk of diabetes. Previous research showed low rates of awareness, treatment and control of diabetes in China 10 . Fujian province, in southeast China, is a high‐prevalence area of cerebrovascular disease.…”
Section: Introductionmentioning
confidence: 96%